Preparation and Evaluation of a Poly-herbal Sheet Mask for Enhanced Skin Care Applications - Roma Rupesh Kasar; Dr. Bhalke Rasika; Phad Pratiksha Kailas; Shaikh Parvej Jakir; Gaikwad Akshada Mangesh; Dr. Mahendra Giri (Asian Journal of Pharmaceutical Research and Development, 2026)
Herbal cosmetics have gained significant attention due to their safety, efficacy, and minimal side effects. The present study aims to formulate and evaluate a polyherbal face sheet mask using natural ingredients such as neem, turmeric, green tea, rose powder, aloe vera gel, and vitamin E. Sheet masks are facial masks made of fabric soaked in nutrient-rich solution that enhances skin hydration and delivers active ingredients effectively. The objective of this study was to prepare a herbal sheet mask and evaluate its physicochemical properties and Stability.The formulation was prepared by combining powdered herbal ingredients with a gel base and then soaking sheet mask into the mixture.The prepared formulation was evaluated for parameters such as pH, viscosity, spreadability,skin irritation and stability. The results showed that the formulation possesses good moisturizing, antimicrobial, and soothing properties. Hence, it can be concluded that the herbal face sheet mask is effective, safe, and suitable for skincare applications.